First observations of the McMurdo-South Pole oblique ionospheric HF channel - Chartier, Alex T.; Vierinen, Juha; Jee, Geonhwa (Atmospheric Measurement Techniques, 2020)
We present the first observations from a new low-cost oblique ionosonde located in Antarctica. The transmitter is located at McMurdo Station, Ross Island, and the receiver at Amundsen–Scott Station, South Pole. The system was demonstrated successfully in March 2019, with the experiment yielding over 30 000 ionospheric echoes over a 2-week period. These data indicate the presence of a stable E layer and a sporadic and variable F layer with dramatic spread F of sometimes more than 500 km (in units of virtual height). The most important ionospheric parameter, NmF2, validates well against the Jang Bogo Vertical Incidence Pulsed Ionospheric (VIPIR) ionosonde (observing more than 1000 km away). GPS-derived TEC data from the Multi-Instrument Data Analysis Software (MIDAS) algorithm can be considered necessary but insufficient to predict 7.2 MHz propagation between McMurdo and the South Pole, yielding a true positive in 40 % of cases and a true negative in 73 % of cases. The success of this pilot experiment at a total grant cost of USD 116 000 and an equipment cost of ∼ USD 15 000 indicates that a large multi-static network could be built to provide unprecedented observational coverage of the Antarctic ionosphere.